2016
DOI: 10.3389/fpsyg.2016.01534
|View full text |Cite
|
Sign up to set email alerts
|

False-Belief Understanding and Language Ability Mediate the Relationship between Emotion Comprehension and Prosocial Orientation in Preschoolers

Abstract: Emotion comprehension (EC) is known to be a key correlate and predictor of prosociality from early childhood. In the present study, we examined this relationship within the broad theoretical construct of social understanding which includes a number of socio-emotional skills, as well as cognitive and linguistic abilities. Theory of mind, especially false-belief understanding, has been found to be positively correlated with both EC and prosocial orientation. Similarly, language ability is known to play a key rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 64 publications
(100 reference statements)
2
13
0
3
Order By: Relevance
“…They too found a correlation between understanding of the external causes of emotion and ToM. Similar findings emerged from a study carried out by Ornaghi et al (2016) in the same age range as the participants in Weimer and colleagues’ research. Focusing on how language and false-belief understanding mediate the influence of emotion comprehension on prosocial orientation, the authors reported positive significant correlations between EU and ToM, even when the effects of age and gender had been controlled for.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…They too found a correlation between understanding of the external causes of emotion and ToM. Similar findings emerged from a study carried out by Ornaghi et al (2016) in the same age range as the participants in Weimer and colleagues’ research. Focusing on how language and false-belief understanding mediate the influence of emotion comprehension on prosocial orientation, the authors reported positive significant correlations between EU and ToM, even when the effects of age and gender had been controlled for.…”
Section: Introductionsupporting
confidence: 76%
“…The effects of gender have been assessed in some but not all of the studies investigating children’s social cognition. In general, when gender has been controlled for, it has been found to make little (e.g., Kårstad et al, 2015 ) or no contribution (e.g., Pons et al, 2002 , 2004 ; Pons and Harris, 2005 ; Grazzani et al, 2015 ; Ornaghi et al, 2016 ) to explaining variance in EU. In a recent study with a sample of 3- to 8-year-old children, Fidalgo et al (2017) found that EU was unaffected by gender in relation to eight out of the nine components of emotion understanding assessed by the TEC.…”
Section: Introductionmentioning
confidence: 99%
“…Новейшие данные о взаимосвязи понимания эмоций и просоциальной ориентации в дошкольном возрасте, полученные в эмпирическом иссле-довании Вероники Орнаги с коллегами из Миланского университета Бико-кка (V. Ornaghi et al, 2016), позволили выявить такие значимые перемен-ные, опосредующие отношения между пониманием эмоций и просоциаль-ным поведением детей 4-6 лет, как языковая способность и понимание ложных убеждений [88]. Комплексная процедура диагностики включала в себя:…”
Section: роль понимания эмоций и модели психического в развитии просоunclassified
“…Во-первых, осознание до-школьниками мыслей, намерений и убеждений других людей позволяет им лучше связывать эмоции и чувства людей с их намерениями и поведением, точно различать трудности собеседника в той или иной ситуации, что в свою очередь может способствовать проявлению эмпатии и просоциаль-ному поведению. Во-вторых, с помощью языка как системы символиче-ской связи дошкольники могут участвовать в социальном взаимодействии, диалоге, воображаемой игре, рассказывании историй и других видах дея-тельности, которые усиливают принятие перспективы, то есть видение си-туации с позиции других людей [88].…”
Section: роль понимания эмоций и модели психического в развитии просоunclassified
“…, (Sales, Fivush, & Peterson, 2003;Van Bergen & Salmon, 2010), , (Ruffman, Slade, Devitt, & Crowe, 2006;Thompson & Winer, 2014), (Wang & Fivush, 2005), (Wang & Fivush, 2005), (Thompson & Winer, 2014) . , Ornaghi, Agliati, & Brazzelli, 2016;Ornaghi, Pepe, & Grazzani, 2016). (Brownell, Svetlova, Anderson, Nichols, & Drummond, 2013;Thompson & Winer, 2014), (Laible & Thompson, 2000).…”
Section: Introductionmentioning
confidence: 99%